Reducing hypersensitivity reactions with HLA-B∗5701 genotyping before abacavir prescription: Clinically useful but is it cost-effective in Singapore? - Kapoor R. (Lippincott Williams and Wilkins, 2016)
10.1097/FPC.0000000000000107